2007
DOI: 10.1242/jcs.010348
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of P2X4 receptors by lysosomal targeting, glycan protection and exocytosis

Abstract: The P2X4 receptor has a widespread distribution in the central nervous system and the periphery, and plays an important role in the function of immune cells and the vascular system. Its upregulation in microglia contributes to neuropathic pain following nerve injury. The mechanisms involved in its regulation are not well understood, although we have previously shown that it is constitutively retrieved from the plasma membrane and resides predominantly within intracellular compartments. Here, we show that the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
231
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(256 citation statements)
references
References 65 publications
21
231
0
4
Order By: Relevance
“…In contrast, the lysomotropic compound, chloroquine [24], rapidly increased P2X 4 R currents. Our results are in accord with a recent study showing that other lysomotropic agents increased surface expression of P2X 4 R in macrophages [17] and suggest that alterations in endocytic and lysosomal trafficking pathways are primarily responsible for the regulation of functional P2X 4 R in macrophages. Phagocytosis is one of the most important innate effector functions of macrophages, serving to clear particulate matter, apoptotic cells and bacteria [32].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, the lysomotropic compound, chloroquine [24], rapidly increased P2X 4 R currents. Our results are in accord with a recent study showing that other lysomotropic agents increased surface expression of P2X 4 R in macrophages [17] and suggest that alterations in endocytic and lysosomal trafficking pathways are primarily responsible for the regulation of functional P2X 4 R in macrophages. Phagocytosis is one of the most important innate effector functions of macrophages, serving to clear particulate matter, apoptotic cells and bacteria [32].…”
Section: Discussionsupporting
confidence: 93%
“…These results allow us to conclude that the ATP-evoked currents we record under these conditions result solely from activation of P2X 4 R. P2X 4 R in resting macrophages was predominantly localized to lysosomal compartments as indicated by co-localization of P2X 4 R and the lysosomal marker, CD68 (Fig 2A). In agreement with the previous study on mouse peritoneal macrophages [17], we found that agents that induce lysosomal secretion increase P2X 4 Rmediated membrane currents (Fig. 2C).…”
Section: P2x 4 R Protein and Functional Expression In Unstimulated Masupporting
confidence: 93%
See 1 more Smart Citation
“…Surprisingly, a large amount of P2X4R protein within microglia (and macrophages) localizes predominantly to intracellular lysosomal compartments71, and P2X4R protein remains stable within the proteolytic environment of lysosomes. How P2X4R protein is recruited to the cell surface of microglia remains elusive, but recent studies have shown that trafficking of P2X4R protein to the cell surface occurs when microglia are stimulated by a toll‐like receptor 4 agonist, lipopolysaccharide72, 73, or the Ca 2+ ionophore, ionomycin71. Furthermore, the chemokine CCL2 increased P2X4R protein levels on the cell surface (without changing total cellular expression) through chemotactic cytokine receptor 274.…”
Section: Spinal Microglia Are Crucial For Neuropathic Painmentioning
confidence: 99%
“…The early hints and recent evidence for localization of purinoceptors on intracellular sites, including lysosomes [2][3][4], mitochondria [5,6] and in nuclei where they open ion channels and appear to influence mRNA activity [7,8], offers up a whole new aspect of purinergic signalling.Purinergic signalling, ATP acting as an extracellular signalling molecule, was proposed in 1972 [9]. Separate families of purinergic receptors were recognised, named P1 receptors for adenosine and P2 receptors for ATP and ADP [10].…”
mentioning
confidence: 99%